Can we put a Number on it? Design Education Under Capitalism, Science, and Technology - Han, Helen Yaqing (YU-WRITE: Journal of Graduate Student Research in Education, 2022)
In contemporary media contexts, graphic design work no longer focuses solely on the aesthetic or representational functionality of 2-dimensional design artefacts. In response to public expectations, economic imperatives, and dominant STEM narratives embracing technical innovation, design education is gradually reshaping and retooling itself in line with techno-capitalist purposes. Design education is becoming more science-driven, introducing more data-driven research methodologies and positivist approaches such as behaviourism, computer science, design engineering, and interactive design. As the discipline of design continues to evolve, there is a growing debate over whether design-making should fully embrace technology and digital media, displacing traditional design work and curriculum with data science epistemologies that align design education with corporate interests, big data, algorithmic culture, and ‘surveillance capitalism’ (Couldry & Mejias, 2019; Crawford 2021; Zuboff, 2019). This essay provides a critical perspective on current trends in design education sectors that embrace tech-oriented methodologies and design practices. I argue that uncritically translating the discipline of design for digital culture risks exacerbating these equity issues and power relations. Furthermore, this essay discusses what priorities in design education foster critical and even activist forms of creativity alongside building essential design skills as well as technical and aesthetic competences.